The Human Rights Approach in the Attention of Vulnerable Populations in Contexts of Emergency and Disasters of Natural Origin: Experiences in Costa Rica - Méndez, Juan Carlos (2018)
The article discusses the scope, limitations, and experiences in the application of the human rights approach in the attention of vulnerable populations in contexts of emergency and disasters in Costa Rica. This discussion takes, as starting point, recent experiences carried out by Costa Rican institutions in the field of risk and emergency management. It briefly analyzes the development of the concept of the human rights approach in this area. This way, it highlights the efforts of the humanitarian community in the incorporation of measures to ensure that the most vulnerable people, directly affected by a disaster, should have access, without discrimination, to the provision of assistance, especially those populations historically living in conditions of vulnerability such as women, children, people with disabilities, migrants and older people.